2022
DOI: 10.3390/jcm11164857
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Strength and Balance as Mediators in the Association between Physical Activity and Health-Related Quality of Life in Community-Dwelling Older Adults

Abstract: Lower extremity muscle strength (LEMS) and body balance (BB) are essential for older adults to maintain an upright posture and autonomously perform their basic activities of daily living. This study aimed to examine whether LEMS and BB mediate the relationship between physical activity (PA) and health-related quality of life (HRQoL) in a large sample of community-dwelling older adults. This is a cross-sectional study carried out with 802 individuals, 401 males and 401 females (69.8 ± 5.6 years), residents of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 83 publications
1
6
0
5
Order By: Relevance
“…Thus, some participants may have developed FOF, and this feeling has reduced GS [ 72 ] and BB control [ 73 ], co-participating in the occurrence of new fall events, in turn reducing HRQoL [ 67 ]. Our findings also corroborate a previous investigation that pointed to GS, unipodal support, and lower limb strength in older adults (75 years old) as mediators in the relationship between walking habits and HRQoL [ 67 ], as well as an increase in HRQoL due to increased PA levels in the bilateral relationship with an improvement in physical functions, which includes GS and BB [ 30 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, some participants may have developed FOF, and this feeling has reduced GS [ 72 ] and BB control [ 73 ], co-participating in the occurrence of new fall events, in turn reducing HRQoL [ 67 ]. Our findings also corroborate a previous investigation that pointed to GS, unipodal support, and lower limb strength in older adults (75 years old) as mediators in the relationship between walking habits and HRQoL [ 67 ], as well as an increase in HRQoL due to increased PA levels in the bilateral relationship with an improvement in physical functions, which includes GS and BB [ 30 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the relationship between PA and HRQoL, with BB as one of the mediators, other factors must be considered as mediators or moderators. A current study pointed out that in the relationship between PA and HRQoL, BB and lower limb strength mediated the relationship by approximately 47% and 39.6%, respectively [ 30 ]. Moreover, unipedal support and lower limb strength were identified in older adults (75 years) as mediators in the relationship between walking habits and HRQoL [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ulasan ini mengungkapkan bukti kepastian rendah terbaik bahwa latihan penguatan PIFM meningkatkan fungsi kaki selama gaya berjalan dan bukti kepastian yang sangat rendah untuk efek yang menguntungkan pada kontrol keseimbangan dinamis (Willemse et al, 2022). Kekuatan otot ekstremitas bawah (LEMS) dan keseimbangan tubuh (BB) sangat penting bagi orang dewasa yang lebih tua untuk mempertahankan postur tubuh yang tegak dan secara mandiri melakukan aktivitas dasar kehidupan sehari-hari mereka (De Maio Nascimento et al, 2022). tidak ada perbedaan efek yang sangat signifikan antara Balance Strategy Exercise dan Resistance Band Exercise terhadap peningkatan keseimbangan dinamis (Wahyuni, 2018).…”
Section: Pembahasanunclassified
“…Therefore, the lower the gait variability, the lower the chance of falling. In another mediation study developed by the same research group mentioned [ 38 ], the authors verified whether lower limb muscle strength (LEMS) and BB performance mediated the relationship between physical activity level (PA) and health-related quality of life (HRQoL). The results indicated that LEMS and BB mediated the association between PA and HRQoL by approximately 39.6% and 47%, respectively.…”
Section: Introductionmentioning
confidence: 99%